Pengaruh Penggunaan E-Modul Berbasis Hasil Riset pada Tema Konservasi Terhadap Kemampuan Literasi Konservasi Siswa SMP Kelas VII - Indah Eka Wati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to explore the effect of research-based e-modules on students' conservation literacy skills. The method used is a quasi-experimental approach with a nonequivalent control group design. The study involved two groups: an experimental group using the e-module and a control group without the e-module. The research population consisted of 170 seventh-grade students, with a sample of 62 students determined using the Stovin formula. Class VII D was assigned as the experimental group, while Class VII F served as the control group. Conservation literacy skills were measured using test and non-test instruments. Data analysis was conducted using the Independent Sample T-Test, which resulted in a significance value below 0.05. This indicates that the null hypothesis (H₀) was rejected, while the alternative hypothesis (Hₐ) was accepted. Therefore, the use of research-based e-modules has a positive impact on improving the conservation literacy skills of seventh-grade students. Keywords: Research-Based E-Module, Conservation Literacy Skills